2015
DOI: 10.1177/1350650115574734
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of nanoparticle additive impacts on thermohydrodynamic characteristics of journal bearings

Abstract: Thermohydrodynamic behaviors of single-groove journal bearing are assessed operating under steady-state loading. The set of governing equations including continuity, momentum, and energy within the lubricant and energy within the solid bush are simultaneously solved employing the finite volume scheme. The analysis takes into account the cavitation effects and the mixing of the lubricant recirculation. In the present study, the performance of the journal bearing is obtained for two types of lubricant: pure oil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 25 publications
0
34
0
Order By: Relevance
“…As can be seen in the abovementioned articles, there has been numerous studies in literature to improve the performance and design of journal bearings by investigating the effect of different parameters [13]. In particular, the effect of additive nanoparticles is one of main research directions [14]. Nanofluids have recently received much attention due to numerous reports on the dramatic increase in thermal properties [15].…”
Section: Introductionmentioning
confidence: 99%
“…As can be seen in the abovementioned articles, there has been numerous studies in literature to improve the performance and design of journal bearings by investigating the effect of different parameters [13]. In particular, the effect of additive nanoparticles is one of main research directions [14]. Nanofluids have recently received much attention due to numerous reports on the dramatic increase in thermal properties [15].…”
Section: Introductionmentioning
confidence: 99%
“…Their experimental finding revealed that nano CuO-based bio-lubricant exhibited outstanding wear and friction reduction behavior compared to synthetic lubricants as well as other nano-based bio-lubricants. Solghar 8 theoretically investigated the thermo-hydrodynamic characteristics of journal bearings using pure oil and pure oil blended with Al 2 O 3 nanoparticles and presented various results such as side leakage, load-carrying capacity, friction coefficient, temperature and pressure distributions. It was found that the lubricant with nano-additives increases both the load-carrying capacity and the friction coefficient and decreases the flow rate compared to the pure oil.…”
Section: Introductionmentioning
confidence: 99%
“…Also, in order to assess the impacts of turbulent conditions on the bearing THD performance, a modified low-Re k–ε turbulence model was used. 11–18…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Moreover, the heat transfer in the grooves was modeled in their studies. Most recently, Arab Solghar et al [8][9][10][11][12][13][14][15][16][17][18] have extensively investigated the THD performance of journal bearings for both laminar and turbulent flow in the bearing. They experimentally examined the THD behavior of a twin groove journal bearing under variable load angle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation